Spectral Characteristics of Some Arylazopyrazolones - El-Haty, M.T. (Asian Journal of Chemistry, 2010)
Electronic, IR and 1H NMR spectroscopy were made to investigate the role of the molecular structure and of the solvent polarity on the spectral properties of some arylazopyrazoline-5-ones. Based on the spectral shifts in pure organic solvents and buffer solutions, the absorption bands observed in the UV and visible spectra of the studied compounds have been assigned. The IR and 1H NMR spectra confirmed that the compounds exist as hydrazo-keto structure. Further, the pkα values were determined using spectrophotometric and potentiometric methods.